Prevalence of Obesity in Young Patients with Severe Haemophilia and Its Potential Impact on Factor VIII Consumption in Germany - Olivieri, Martin; Königs, Christoph; Heller, Christine; Horneff, Silvia; Oldenburg, Johannes; Halimeh, Susan; Kentouche, Karim; Knöfler, Ralf; Fischer, Lars; Pfrepper, Christian; Kurnik, Karin; Bidlingmaier, Christoph (Hämostaseologie, 2019)
Similar to the general population, overweight and obesity have increasingly become a medical and economic burden also in patients with haemophilia in industrialized nations. In this study in seven German haemophilia centres, we identified a prevalence of overweight and obesity of 25.2% among 254 young patients <30 years (median: 13 years; range: 0–30 years) with severe haemophilia A and without a history of inhibitors. The median FVIII dosage based on bodyweight was significantly higher in normal weight compared with overweight or obese patients (96.9 vs. 72.9 IU/kg/week, respectively; p < 0.0001). This suggests that an individualized dosing regime which might be based on FVIII pharmacokinetics, physical activity and pre-existing haemophilic arthropathy is applied rather than dosing by bodyweight only. The bleeding rates observed in obese (median: 1; range: 0–17) versus normal weight patients (median: 2; range: 0–28) did not differ significantly (p = 0.057). Lower bleeding rates might be due to reduced activity or expected higher FVIII plasma levels in overweight patients. Due to the increasing prevalence of overweight/obesity in patients with haemophilia an interdisciplinary approach for individualized haemophilia treatment and weight loss programmes might be helpful for optimal and economical treatment for this group of patients.
Keywords: severe haemophilia; overweight; obesity; economic burden; factor VIII consumption